Pengembangan UMKM Unggulan Gambo Muba Produk Lokal Guna Menopang Perekonomian Rakyat Akibat COVID-19 - Lesi Hertati; Irlan Feri; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Indonesia Berdaya, 2021)
Abstract: Gambo Muba is a product of micro, small, and medium enterprises originating from the Musi Banyuasin community, which comes from Gambir sap waste which is used to give jumputan fabric colors. The way of making it is indeed not easy, the craftsman must know the fashion traditions of the toy in order to achieve good results. The motifs are tailored to market needs and according to buyers' interests, including current trends. For the manufacture itself, awareness and knowledge are needed to preserve the Gambo Muba jumputan culture. Especially the local craftsman level because this craft is done manually or by hand. Jumputan's typical Gambo fabric, which is a type of jumputan that is done with a tie-dye technique to create interesting color gradations. Not written in a wax-like batik in general, the cloth will be tied and then dyed in color. The gambo Muba UMKM survey was conducted on micro, small, and medium enterprises in Musi Banyuasin Regency, South Sumatra, Indonesia. The results of community service that we surveyed were people who made Gambo Muba's micro, small, and medium-sized business products during the Covid-19 season very much to help people's household lives during the Covid-19 season where all residents on earth had to lockdown, to reduce the spread of the Covid-19 virus.  Abstrak: Gambo Muba adalah produk usaha mikro kecil menengah  asli masyarakat Musi Banyuasin, yang berasal dari limbah getah Gambir dimanfaatkan untuk memberi corak warna kain jumputan. Cara pembuatanya memang tak mudah, pengrajin harus tahu akan tradisi mode perkainan agar dapat mewujudkan hasil yang baik. Motifnya disesuaikan dengan kebutuhan pasaran dan sesuai minat pembeli, termasuk trend kekinian. Untuk pembuatannya sendiri, diperlukan kesadaran dan ilmu pengetahuan guna melestarikan budaya jumputan Gambo Muba. Terutama tingkat pengrajin lokal karena kerajinan ini dikerjakan secara manual alias pakai tangan. Kain Gambo khas Jumputan, yaitu jenis jumputan yang dikerjakan dengan teknik ikat celup untuk menciptakan gradasi warna yang menarik. Tidak ditulis dengan malam seperti batik pada umumnya, kain akan diikat lalu dicelupkan ke dalam warna.  Survey UMKM gambo Muba ini dilakukan pada usaha mikro kecil menengah  di Kabupaten Musi Banyuasin Sumatera Selatan-Indonesia. Hasil Pengabdian Pada Masyarakat  yang kami survey adalah masyarakat yang membuat produk usaha mikro kecil menengah  Gambo Muba pada musim Covid-19 sangat membantu kehidupan rumah tangga  masyarakat pada musim Covid-19 dimana seluruh penduduk di muka bumi harus lockdown, guna mengurangi penyebaran virus Covid-19.